Estrogen as an adjuvant therapy to antipsychotics does not prevent relapse in women suffering from schizophrenia: results of a placebo-controlled double-blind study - Bergemann, Niels; Mundt, Christoph; Parzer, Peter; Pakrasi, Manoshi; Eckstein-Mannsperger, Ursula K.; Haisch-Gomes, Susanne; Salbach, Birgit; Klinga, Klaus; Runnebaum, Benno; Resch, Franz (Schizophrenia research, 2005)
The expected therapeutic effect of estrogen as an adjunct treatment to antipsychotics in women suffering from schizophrenia for relapse prevention was to be tested under real-life conditions. A multicenter, randomized, placebo-controlled, double-blind, cross-over study based on an A-B-A-B (and/or B-A-B-A) design was applied. Forty-six hypoestrogenic women with schizophrenia hospitalized for the first time or repeatedly were included in the study. Their average age was 37.9 and they had been suffering from schizophrenia for 8.4 years. During the drug treatment phases, they received a three-phase estrogen-gestagen combination drug (17β-estradiol+norethisterone acetate) in addition to an antipsychotic drug. Significant effects of the adjuvant hormone replacement therapy on the estradiol levels could be observed, and high and low levels of estradiol prevailed in the active drug and placebo phases, respectively. We did not find any difference either in defined relapse events or in the psychopathology between estradiol replacement and placebo phases. Neither did the required antipsychotic doses or the tolerance data differ between the two phases. Thus, the results of our study do not confirm the hypothesis that a combined estradiol/antipsychotic therapy is superior to an antipsychotic monotherapy for relapse prevention.
Gesehen am 15.12.2020